Cellulose acetate nanofiber electrospun on nylon substrate as novel composite matrix for efficient, heat-resistant, air filters. (22nd October 2016) - Nicosia, A.; Keppler, T.; Müller, F.A.; Vazquez, B.; Ravegnani, F.; Monticelli, P.; Belosi, F.
Abstract: Cellulose acetate (CA) nanofibers were prepared via electrospinning to obtain a high quality factor (QF) fibrous mat for aerosol particle filtration. To this purpose, special attention was paid to the substrate material used to collect the nanofibers. Different materials (glassine paper, Lyocell, nylon grids) were investigated for use as substrates in the membrane spinning process. Membrane and membrane fiber morphologies were characterized by optical microscope and scanning electron microscope (SEM) analyses. Results show that the arrangement of the membrane fibers is directly correlated to the morphology of the collecting substrate material. Experiments shows that the electrospun nanofiber web tends to recreate the specific character of the supporting textile texture. A support with a pronounced bi-dimensional structure should be preferred. A regular grid, made of nylon, is selected for the composition with CA nanofibres. By maintaining the same support, various electrospinning parameters such as the spinning solution CA concentration (14 wt%, 18 wt%) and spinning volume (15–120 μL) of the membranes are tested in terms of air filtration performance. Filtration tests are performed by measuring the filter penetration against neutralized aerosol particles. Basis weight, solid volume fraction and thickness parameter were investigated to find the best arrangement. The filtration efficiency of stacked layers is analyzed at variable thickness of the building block element. An electrospun membrane of above 60 μm thickness, combined with the selected substrate, increases the QF and improve its reproducibility. The QF can be further increased with an optimized porosity of the nylon substrate. The best QF of 0.080±0.050 Pa −1 at 300 nm was obtained by spinning a 14 wt% CA solution in an acetone- DMSO-acetic acid solvent mixture on a nylon grid with 100 μm mesh size producing fleeces with a very low pressure drop (7 Pa). Thermogravimetric analyses (TGA) and SEM imaging demonstrated the stability of the composite filter morphology up to 200 °C. Highlights: Morphology characterization of electrospun cellulose acetate nanofibers. Improvement of cellulose acetate nanofibers composite with nylon substrate. Quality factor at different spinning volume, CA concentration and substrate mesh. Analysis of the multilayer structure at variable building block elements. Investigation of the thermal stability of the final filter up to 200 °C.